A kind of spheroidal iron-manganese oxide composite material and its preparation method
Patent Information
- Application Number
- CN202611469405.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
上述形貌差异不仅会降低同批次粉体结构的一致性,还容易使颗粒在后续混合、分散和成型过程中产生局部架桥、孔隙分布不均及颗粒接触状态离散等问题,从而不利于获得较均匀的颗粒堆积和稳定的压实状态
1)本发明通过协同控制类球形颗粒数量占比、二维投影长短轴比及投影圆度,使粉体中较高比例的颗粒具有方向性较弱、轮廓较为连续和规整的类球形主体。该颗粒形貌能够减少细长、不规则或棱角化颗粒在堆积和受压过程中产生的局部架桥及非均匀支撑,使颗粒具有较好的空间重排条件。实施例与第一阶段沉淀剂快速加入的对比例相比,类球形颗粒比例以及振实密度和定压压实密度均得到明显改善,说明对颗粒主体轮廓进行调控有利于提高粉体堆积和压实状态。
Smart Images

Figure REF-OBJ-1789094069781-000001 
Figure REF-OBJ-1789094069781-000002 
Figure REF-OBJ-1789094069781-000003
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic functional materials and metal oxide composite materials, specifically to a spherical iron-manganese oxide composite material and its preparation method. Background Technology
[0002] Iron and manganese are both transition metals with multiple valence states. Iron-manganese oxide composites, formed from iron and manganese oxides, exhibit physicochemical properties different from those of single metal oxides, making them valuable for research and application in environmental treatment, catalysis, and electrochemical energy storage. Iron-manganese oxide composites are typically prepared through precipitation, hydrothermal processes, oxidation reactions, heat treatment, or a combination of these processes. Different raw material systems and reaction conditions affect the nucleation, growth, and aggregation processes of the resulting powders, thereby altering particle size, overall profile, particle size distribution, and surface state. For powder materials requiring further dispersion, shaping, or the construction of electrochemical reaction interfaces, the aforementioned particle structure further influences the arrangement, packing, contact, and interfacial interactions between particles.
[0003] Chinese patent CN104815609A discloses an iron-manganese composite oxide, its preparation method, and its application. The method involves reacting a ferrous sulfate heptahydrate solution with a potassium permanganate solution, followed by hydrothermal treatment, aging, drying, and grinding to obtain the iron-manganese composite oxide powder. This iron-manganese composite oxide consists of short rod-shaped nanoparticles with a length of 100 to 120 nm and a width of 50 to 60 nm, and is primarily used for the adsorption of hexavalent chromium ions in water.
[0004] Chinese patent CN103212364A discloses an iron-manganese composite oxide, its preparation method, and its application in arsenic removal from water. The method involves treating natural iron-manganese ore with sulfuric acid solution to adjust the iron-manganese ion ratio, followed by sodium carbonate precipitation, filtration, drying, and calcination to obtain the iron-manganese composite oxide. This technology primarily adjusts the arsenic removal performance of the material by controlling the iron-manganese composition and preparation conditions.
[0005] Existing research on iron-manganese oxide composites has largely focused on elemental composition, crystal phase structure, preparation conditions, and specific performance characteristics, while relatively little attention has been paid to the synergistic relationship between the overall particle profile, particle size distribution, and surface microstructure. In actual preparation processes, different particles are prone to significant differences in shape, discrete particle size distribution, local agglomeration, or the formation of needle-like, rod-like, or plate-like extended structures. These morphological differences not only reduce the consistency of the powder structure within the same batch but also easily lead to problems such as local bridging, uneven pore distribution, and discrete particle contact states during subsequent mixing, dispersion, and molding processes, thus hindering the achievement of uniform particle packing and stable compaction.
[0006] Therefore, existing iron-manganese oxide composite materials not only suffer from difficulties in simultaneously achieving regularity in particle outline, particle size distribution, and surface structure, but also lack a preparation pathway that can synergistically regulate these structures at the nucleation, growth, ripening, and heat treatment stages. Relying solely on single precipitation or conventional heat treatment conditions easily leads to an increase in irregular particles, difficulty in forming particle size gradations, or weakening of subtle surface undulations. Therefore, it is necessary to establish a staged preparation process corresponding to the target particle structure, achieving a high proportion of near-spherical particles while simultaneously realizing a reasonable particle size distribution and appropriate surface undulations. This improves the powder's packing and compaction state and provides a structural basis for particle contact and subsequent interfacial interactions. Summary of the Invention
[0007] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a spherical iron-manganese oxide composite material and its preparation method. By synergistically limiting the proportion of spherical particles, the two-dimensional projected profile, the particle size distribution, and the surface granular undulations, the material possesses a relatively regular spherical body, controlled particle size, and a suitable surface fine structure. Furthermore, through particle size matching between particles of different sizes, larger and smaller particles can form a positional relationship within the particle group that facilitates filling. During the preparation process, the nucleation, growth, and surface structure formation processes of particles are controlled in stages through the first stage of continuously and controlled addition of a precipitant at a high stirring speed, the second stage of reducing the stirring speed and gradually increasing the pH, and subsequent curing and segmented heat treatment. This reduces irregular particles, unbalanced particle size distribution, and excessive surface sintering, improves the accumulation and compaction of the powder, and retains the fine surface structure while maintaining the regularity of the particle body, providing a structural basis for subsequent particle contact and interfacial interactions.
[0008] This invention provides a near-spherical iron-manganese oxide composite material, wherein the composite material is a powder whose chemical composition includes iron, manganese and oxygen elements, and the powder contains near-spherical particles.
[0009] Based on the total number of particles with identifiable outer contours in scanning electron microscope images, the proportion of the spherical particles is not less than 50%.
[0010] The ratio of the major axis a to the minor axis b of the two-dimensional projected outer contour of the spherical particle obtained by ellipse fitting is 1.00 to 1.50, and the surface of the spherical particle has a granular undulating texture composed of fine protrusions.
[0011] Iron, manganese, and oxygen constitute the basic chemical composition of the composite powder. Spherical particles comprise at least 50% of the particles with identifiable outer contours, resulting in a powder body composed of particles with relatively weak directionality and regular contours. The aspect ratio further limits the degree to which particles deviate from their near-circular contours, facilitating more uniform spatial rearrangement during particle stacking. Simultaneously, the granular undulation texture formed by fine protrusions imparts a moderate surface roughness without disrupting the spherical main body contour, allowing the material to balance a relatively regular particle body with a surface structure featuring subtle undulations.
[0012] Preferably, the number of spherical particles accounts for no less than 70% of the total number of particles whose outer contours can be identified in the scanning electron microscope image.
[0013] A quantity ratio of no less than 70% ensures that most identifiable particles have a spherical shape, which reduces the disturbance of a small number of irregular particles to the overall packing state. This makes it easier for the particle group to form a relatively uniform arrangement and contact relationship during mixing, compaction or molding, thereby improving the consistency of the main structure of the powder.
[0014] Preferably, the ratio of the major axis a to the minor axis b of the two-dimensional projected outer contour of the spherical particle obtained by ellipse fitting is 1.00 to 1.30.
[0015] When the major-minor axis ratio is between 1.00 and 1.30, the two principal axis dimensions of the particle's two-dimensional projection are closer, which can reduce the obvious directionality of the particle and the local bridging tendency caused by its slender shape, so that the particles have a more uniform geometric basis during mutual contact and force rearrangement.
[0016] Preferably, the projected roundness C of the quasi-spherical particles is 0.70 to 1.00, where C = 4πA / P. 2 Where A is the two-dimensional projected area of the spherical particle, and P is the two-dimensional projected outer contour perimeter of the spherical particle.
[0017] A projected roundness C of 0.70–1.00 can further constrain the curvature of the particle's outer contour and local irregular boundaries, ensuring that the particles maintain a relatively continuous and gently rounded shape. This contour feature helps reduce local point contact and non-uniform support caused by sharp edges or highly tortuous boundaries, and together with the aspect ratio, improves the geometric consistency of near-spherical particles during the stacking and contact process.
[0018] Preferably, based on the number of the quasi-spherical particles, at least 80% of the quasi-spherical particles have an equivalent circular diameter of 0.10 to 3.50 μm, and the equivalent circular diameter De = 2√(A / π).
[0019] At least 80% of the near-spherical particles are within the equivalent circular diameter range of 0.10–3.50 μm, which can limit the particle size dispersion caused by excessive ultrafine or coarse particles, keeping the main particle group within a controlled micron-scale range. This helps to reduce local agglomeration and large-sized pores caused by excessively large particle size spans, providing a particle size basis for forming a more uniform particle packing structure.
[0020] Preferably, based on the number of the spherical particles, at least 60% of the spherical particles have an equivalent circular diameter of 0.30 to 3.20 μm.
[0021] At least 60% of the near-spherical particles are located within the equivalent circular diameter range of 0.30–3.20 μm, further concentrating the main particle size group in the powder within this micrometer scale range. This relatively concentrated main particle size range within the overall particle size boundary facilitates the establishment of a stable main particle skeleton, allowing the remaining smaller particles to play a supplementary filling and contact role in the interparticle spaces or on the particle surface.
[0022] Preferably, the projected lateral dimension of the surface protrusions forming the granular undulating texture is 20–200 nm.
[0023] The projected lateral dimensions of 20–200 nm make the surface protrusions significantly smaller than the overall size of the near-spherical particles. Multiple fine protrusions can form a granular rough surface while maintaining the main near-spherical outline. Compared to a completely smooth particle surface, these fine undulations can increase the contact points between the particles and the surrounding medium or adjacent components, providing a more sufficient surface structure basis for subsequent interfacial interactions, while avoiding the formation of excessively large sharp protrusions.
[0024] Preferably, the ratio of the average projected lateral dimension of the surface protrusion to the average equivalent circle diameter of the spherical particle is 0.05 to 0.20.
[0025] The size ratio relates the local surface protrusion to the overall particle diameter. A range of 0.05 to 0.20 allows the protrusion to remain a local surface structure within the overall particle scale, avoiding excessively large protrusions that would disrupt the spherical main body outline, while maintaining a moderate granular roughness on the surface, thus balancing particle packing regularity and surface structure characteristics.
[0026] Preferably, in scanning electron microscope images at magnification of 10,000x or higher, the surface of the quasi-spherical particles does not have radially extending needle-like, rod-like, or sheet-like structures with a length greater than 300 nm and a ratio of the projected major axis to the projected minor axis greater than 3.
[0027] By limiting the projected length and the ratio of the projected major axis to the projected minor axis of the radially extending structure, the particle surface is mainly composed of short-scale fine protrusions, avoiding the formation of obvious long needle-like, rod-like, or sheet-like structures. This reduces the interlocking, bridging, and local support effects caused by the slender extending structure during particle stacking, allowing the spherical body to participate more fully in interparticle contact, while preserving the surface interface features brought about by the fine undulations.
[0028] Preferably, the frequency distribution of the equivalent circular diameter of the quasi-spherical particles has two particle size concentration regions located in the ranges of 0.10–0.80 μm and 0.80–3.50 μm, respectively; quasi-spherical particles with equivalent circular diameters in the range of 0.80–3.50 μm are designated as first-size particles, and quasi-spherical particles with equivalent circular diameters in the range of 0.10–0.80 μm are designated as second-size particles, wherein particles with an equivalent circular diameter equal to 0.80 μm are classified as second-size particles; the ratio of the average equivalent circular diameter of the first-size particles to that of the second-size particles is 2.0–10.0:1.
[0029] Preferably, based on the number of particles of the second diameter in the two-dimensional projection image of a scanning electron microscope, at least 35% of the two-dimensional projection outlines of the particles of the second diameter are connected to the two-dimensional projection outlines of the particles of the first diameter, or their two-dimensional projection centroids are located in the interval region between the two-dimensional projection outlines of adjacent particles of the first diameter.
[0030] The two particle size concentration zones mentioned above represent the coexistence of smaller and larger particle groups on a statistical scale, and do not require all particles to form two completely separate monodisperse particle size groups. The larger first-size particles can form the main particle skeleton, while the smaller second-size particles are connected or spaced apart from the first-size particles in a two-dimensional projection. This creates a positional fit between particles of different sizes with a certain statistical proportion, which is beneficial for smaller particles to fill the local gaps between larger particles, thereby improving the spatial filling state of the particle group.
[0031] Limiting the proportion of particles of the second diameter in the aforementioned two-dimensional projected positional relationship to no less than 35% avoids statistical bias caused by the accidental appearance of only a small number of small particles, and ensures that the positional relationship between particles of different sizes has a certain degree of group representativeness. The two-dimensional projected positional relationship is used to characterize the morphology and positional relationship of the particle group, and is not equivalent to the direct measurement of the three-dimensional continuous contact network of particles or the actual contact area.
[0032] The present invention also provides a method for preparing the above-mentioned spherical iron-manganese oxide composite material, comprising: adding divalent manganese salt and trivalent iron salt to water, and adding a complexing agent and a dispersing component to form a metal salt solution; wherein the divalent manganese salt is manganese sulfate monohydrate, and the trivalent iron salt is ferric sulfate nonhydrate or ferric nitrate nonhydrate, and the molar ratio of Mn to Fe is 4.8:1 to 13.8:1 based on the amount of Mn and Fe; the mass ratio of the total mass of the divalent manganese salt and trivalent iron salt to the mass of water is 12:(50 to 100); based on the total mass of the divalent manganese salt and trivalent iron salt, the amount of complexing agent is 9.5% to 13.0%, and the amount of dispersing component is 1.0% to 1.5%, wherein the complexing agent is selected from at least one of sodium citrate, sodium tartrate, sodium gluconate, and disodium ethylenediaminetetraacetate, and the dispersing component is selected from at least one of polyvinylpyrrolidone, polyethylene glycol, and sodium polycarboxylate; The total amount of ammonium bicarbonate used is in a ratio of 1.15:1 to the total amount of manganese and iron. Under stirring conditions of 48–55°C and 600–700 r / min, 35%–50% of the total amount of ammonium bicarbonate solution is continuously added over 40–120 min, and the pH of the system is controlled to 6.6–6.9 by adding ammonia water for the first stage of co-precipitation. Subsequently, the stirring speed is reduced to 180–220 r / min, and the remaining ammonium bicarbonate solution is continuously added over 90–180 min, and the pH of the system is gradually increased from the pH of the first stage to 7.8–8.3 by adding ammonia water during the addition process for the second stage of co-precipitation. The resulting precursor slurry is concentrated, matured, separated from solids and liquids, washed and dried, and then subjected to a first stage of heat treatment at 180–230°C, followed by a second stage of heat treatment at 360–480°C to obtain the spherical iron-manganese oxide composite material.
[0033] In the first stage of co-precipitation, a portion of ammonium bicarbonate is continuously and controlledly added at a high stirring speed. This helps to reduce the local instantaneous supersaturation during the addition of the precipitant, thereby reducing irregular rapid precipitation and non-uniform growth, and thus providing conditions for the formation of more regular spherical particles. In the second stage, the stirring speed is reduced and the remaining ammonium bicarbonate is continuously added, while the pH of the system is gradually increased. This causes the subsequent precipitation and particle growth state to differ from that in the first stage, which is conducive to the formation of a particle size distribution and a particle size concentration zone where particles of different sizes coexist. The aging process further promotes the stability of the precursor particle structure. The segmented heat treatment controls the degree of high-temperature sintering while realizing the transformation of the precursor into oxide, so that the outline of the particle body can be maintained and the fine granular surface undulations of the 20-200 nm scale can be preserved.
[0034] Preferably, in the first stage of co-precipitation, under conditions of 48–52°C and 600–650 r / min, 40%–50% of the total amount of ammonium bicarbonate solution is continuously added within 50–80 min, and the pH of the system is controlled to be 6.7–6.9 by adding ammonia.
[0035] Preferably, in the second stage of co-precipitation, the remaining ammonium bicarbonate solution is continuously added within 90 to 120 minutes, and during the addition process, the pH of the system is gradually increased from 6.7 to 6.9 to 8.0 to 8.3 by adding ammonia.
[0036] Preferably, the segmented heat treatment involves first holding the temperature at 210–230°C for 50–60 minutes, then raising the temperature to 440–480°C and holding it for 90–120 minutes.
[0037] The present invention, by adopting the above technical solution, has the following beneficial effects: 1) This invention, through the synergistic control of the proportion of spherical particles, the aspect ratio of the two-dimensional projection, and the projected roundness, enables a higher proportion of particles in the powder to possess a spherical body with weaker directionality and a more continuous and regular outline. This particle morphology can reduce local bridging and non-uniform support caused by slender, irregular, or angular particles during accumulation and compression, thus providing better spatial rearrangement conditions for the particles. Compared with the comparative example where the precipitant was added rapidly in the first stage, the proportion of spherical particles, as well as the tap density and constant pressure compaction density, were significantly improved in the example, indicating that controlling the outline of the particle body is beneficial to improving the powder's accumulation and compaction state.
[0038] (2) This invention controls the overall particle size distribution of spherical particles and creates concentrated areas of different particle sizes with a certain average particle size ratio between larger and smaller particles. Simultaneously, a certain proportion of particles of the second size form a positional relationship of contact or spacing with particles of the first size in the two-dimensional projection of a scanning electron microscope. This allows the larger particles to serve as the main particle skeleton, while the smaller particles fill the local spaces between them. Compared to samples without the aforementioned particle size hierarchy, samples with this particle size matching exhibit higher tap density and constant pressure compaction density, indicating that a reasonable particle size distribution and positional matching are beneficial for improving the space filling degree and compaction density of the particle group.
[0039] (3) This invention controls the fine protrusions on the surface of quasi-spherical particles to a scale of 20–200 nm, and maintains an appropriate ratio between the average projected lateral dimension of the surface protrusions and the average equivalent circle diameter of the quasi-spherical particles, while avoiding the formation of obvious long needle-like, rod-like, or sheet-like radially extending structures. Thus, it can retain the fine undulations on the particle surface while maintaining the quasi-spherical main outline. The fine undulations on the surface are mainly used to provide appropriate surface structure features and the basis for subsequent interfacial interactions, rather than being used directly as a determining factor for increasing the tap density or constant pressure compaction density of powder.
[0040] (4) The present invention employs a combination of processes, namely, the continuous and controlled addition of a portion of ammonium bicarbonate at a relatively high stirring speed in the first stage, the continuous addition of the remaining ammonium bicarbonate and the gradual increase of pH in the second stage, and subsequent aging and segmented heat treatment. This allows different process stages to play a regulatory role in the formation of the particle body, subsequent particle size growth, and surface structure maintenance. If the precipitant is added too quickly in the first stage, the proportion of irregular particles will increase. The lack of a gradual increase of pH in the second stage is not conducive to the formation of a clear particle size hierarchy. If the heat treatment temperature in the second stage is too high, the fine surface undulations will be significantly weakened. Therefore, the above-mentioned segmented process can achieve relatively coordinated control of the target particle body outline, particle size distribution, and surface fine structure in the same powder. Attached Figure Description
[0041] Figure 1 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 1 of the present invention at a magnification of 5000x.
[0042] Figure 2 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 1 of the present invention at a magnification of 10,000.
[0043] Figure 3 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 2 of the present invention at a magnification of 5000x.
[0044] Figure 4 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 2 of the present invention at a magnification of 10,000.
[0045] Figure 5 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 3 of the present invention at a magnification of 5000x.
[0046] Figure 6 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 3 of the present invention at a magnification of 10,000.
[0047] Figure 7 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 4 of the present invention at a magnification of 5000x.
[0048] Figure 8 This is a scanning electron microscope image of the spherical iron-manganese oxide composite material prepared in Example 4 of the present invention at a magnification of 10,000.
[0049] Figure 9 The image shows a scanning electron microscope image of the sample prepared for Comparative Example 1 at a magnification of 20,000.
[0050] Figure 10 The image shows a scanning electron microscope image of the sample prepared for Comparative Example 1 at a magnification of 50,000.
[0051] Figure 11 The image shows a scanning electron microscope image of the sample prepared for Comparative Example 2 at 10,000x magnification.
[0052] Figure 12 The image shows a scanning electron microscope image of the sample prepared for Comparative Example 3 at 10,000x magnification.
[0053] Figure 13 The image shows a scanning electron microscope image of the sample prepared for Comparative Example 3 at 20,000x magnification. Detailed Implementation
[0054] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0055] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0056] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0057] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0058] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0059] Unless otherwise specified, all percentages are by mass, water is deionized water, and room temperature is 25°C.
[0060] The purity of manganese sulfate monohydrate is not less than 99.0%, the purity of ferric sulfate nonhydrate is not less than 98.0%, the purity of ferric nitrate nonhydrate is not less than 98.0%, and the purity of sodium citrate, sodium tartrate, sodium gluconate, disodium ethylenediaminetetraacetate, and ammonium bicarbonate is not less than 99.0%; the weight average molecular weight of polyvinylpyrrolidone is 40,000; the number average molecular weight of polyethylene glycol is 6,000; the number average molecular weight of sodium polycarboxylate is 5,000; and the mass fraction of ammonia is 25%.
[0061] Example 1
[0062] This embodiment discloses a method for preparing a spherical iron-manganese oxide composite material. Through staged co-precipitation, aging and segmented heat treatment, a high proportion of spherical main body, controlled micron-level particle size distribution, two-level particle spatial coordination and fine particulate surface undulation are synergistically formed in the same powder. The specific steps include the following steps.
[0063] S1. Preparation of metal salt solution: By mass, add 9.6 parts of manganese sulfate monohydrate and 2.4 parts of ferric sulfate nonhydrate to 100 parts of water, and stir for 20 min at 25℃ and 500 r / min; add 1.2 parts of sodium citrate, 0.35 parts of sodium tartrate and 0.18 parts of polyvinylpyrrolidone, and continue stirring for 15 min to obtain the metal salt solution.
[0064] S2, First Stage Co-precipitation: Prepare a 1.0 mol / L ammonium bicarbonate solution; heat the metal salt solution to 50℃ and stir at 650 r / min, then add 45% of the total amount of ammonium bicarbonate solution at a uniform rate over 60 min, simultaneously adding ammonia water, and controlling the pH of the system to 6.8. The ratio of the total amount of ammonium bicarbonate to the total amount of manganese and iron is 1.15:1.
[0065] S3, Second stage co-precipitation: Adjust the stirring speed to 220 r / min, add the remaining 55% ammonium bicarbonate solution at a constant rate over 90 min, and adjust the pH of the system from 6.8 to 8.1 at a constant rate using ammonia water; after the addition is complete, continue stirring at 50℃ for 30 min to obtain the precursor slurry.
[0066] S4. Maturation: Concentrate the precursor slurry to a solid content of 26%, heat to 60°C, let stand for 60 min, stir at 150 r / min for 90 min, and then cool to 25°C.
[0067] S5. Solid-liquid separation and drying: The matured slurry was centrifuged at 4000 r / min for 8 min; the resulting solid was washed with water 3 times and then washed with anhydrous ethanol once; the washed solid was vacuum dried at 80℃ for 12 h to obtain the dried precursor.
[0068] S6. Segmented heat treatment: The dried precursor is spread in an alumina crucible with a thickness not exceeding 5 mm. The temperature is increased to 220°C at 2°C / min and held for 60 min in an air atmosphere. Then the temperature is increased to 460°C at 3°C / min and held for 120 min. After being cooled to 25°C in the furnace, it is passed through a 150 μm sieve to obtain the spherical iron-manganese oxide composite material of Example 1.
[0069] Example 2
[0070] This embodiment discloses a spherical iron-manganese oxide composite material with a relatively concentrated main particle size, which illustrates that while maintaining a high proportion of spherical particles and fine surface undulations, the main particles can be concentrated in a relatively narrow micrometer scale range; a small number of small independent particles are allowed in the representative scanning electron microscope field of view, but according to the equivalent circle diameter frequency statistics method specified in this specification, no two particle size concentration areas that meet the judgment conditions are formed.
[0071] The preparation method differs from Example 1 in the following ways: In S1, 10.2 parts of manganese sulfate monohydrate and 1.8 parts of ferric nitrate nonahydrate are added to 100 parts of water, along with 0.95 parts of sodium citrate, 0.22 parts of sodium gluconate, and 0.12 parts of polyethylene glycol; In S2, the temperature is 48°C, the stirring speed is 600 r / min, and 50% of the total ammonium bicarbonate solution is added within 70 min, with a pH of 6.9; In S3, the stirring speed is 200 r / min, and the remaining 50% of the ammonium bicarbonate solution is added within 100 min, with an endpoint pH of 8.0; In S4, the solid content is 24%, the temperature is 58°C, the standing time is 50 min, the stirring speed is 130 r / min, and the stirring time is 100 min; In S6, the mixture is first kept at 210°C for 50 min, and then kept at 440°C for 120 min. The remaining raw materials, operations and conditions are the same as in Example 1; however, the total amount of ammonium bicarbonate is recalculated according to the ratio of its total amount of substance to the total amount of substance of manganese and iron elements of 1.15:1.
[0072] Example 3
[0073] This embodiment discloses an iron-manganese oxide composite material with a relatively low proportion of spherical particles while retaining a two-stage particle size structure and granular surface undulations. This embodiment illustrates that, after deviating from the preferred process conditions of Example 1, the resulting powder can still meet the basic requirements of this invention for a spherical body, particle size structure, and surface undulations, but its particle morphology consistency and packing compaction performance are somewhat reduced compared to Example 1.
[0074] The preparation method differs from Example 1 in the following ways: In S1, 9.0 parts of manganese sulfate monohydrate and 3.0 parts of ferric sulfate nonahydrate are added to 100 parts of water, along with 1.0 part of sodium citrate, 0.30 parts of disodium ethylenediaminetetraacetate, and 0.15 parts of sodium polycarboxylate; In S2, at 55°C and 700 r / min, 40% of the total ammonium bicarbonate solution is added over 40 min, resulting in a pH of 6.7; In S3, the remaining 60% of the ammonium bicarbonate solution is added over 120 min with stirring at 180 r / min, resulting in a final pH of 8.3; In S4, the solid content is 28%, the temperature is 60°C, the standing time is 80 min, the stirring speed is 120 r / min, and the stirring time is 80 min; In S6, the mixture is first kept at 230°C for 60 min, and then kept at 480°C for 90 min. All other operations and conditions are the same as in Example 1; however, the total amount of ammonium bicarbonate is recalculated according to the ratio of its total amount of substance to the total amount of substance of manganese and iron elements of 1.15:1.
[0075] Example 4
[0076] This embodiment discloses a spherical iron-manganese oxide composite material prepared under a combination of process parameters. It primarily illustrates that even under conditions of a low precipitant ratio in the first stage, a long feeding time in the second stage, and a low heat treatment temperature in the second stage, an overall morphology can still be obtained, characterized by predominantly spherical particles, a surface with fine granular undulations, and no obvious needle-like, rod-like, or plate-like radially extending structures. Based on newly obtained representative scanning electron microscope images, this embodiment is no longer considered a quantitative boundary support sample for the particle size ratio condition or the lower limit of the average surface protrusion size ratio described in claim 3. The preparation method differs from Example 1 in the following ways: In S1, the amount of water used is 50 parts; in S2, 35% of the total ammonium bicarbonate solution is added within 120 minutes at 55°C and 650 r / min, resulting in a pH of 6.6; in S3, the remaining 65% of the ammonium bicarbonate solution is added within 180 minutes while stirring at 180 r / min, with a final pH of 7.8; in S4, the solid content is 35%, the temperature is 75°C, the standing time is 120 minutes, the stirring speed is 100 r / min, and the stirring time is 180 minutes; in S6, the mixture is first kept at 180°C for 90 minutes, and then kept at 360°C for 240 minutes. All other raw materials, operations, and conditions are the same as in Example 1; however, the total amount of ammonium bicarbonate is recalculated based on a ratio of its total mass to the total mass of manganese and iron elements of 1.15:1.
[0077] Comparative Example 1 Compared with Example 1, this comparative example only changed the feeding time of 45% of the total amount of ammonium bicarbonate solution in S2 from 60 min to 10 min, while the feeding amount, pH, temperature, stirring speed and other steps remained unchanged.
[0078] Comparative Example 2 Compared with Example 1, this comparative example only omits the pH increase process in S3, keeping the pH of S3 at 6.8 throughout; the amount of feed, feeding time, temperature, stirring speed and other steps in the second stage remain unchanged.
[0079] Comparative Example 3 Compared with Example 1, this comparative example only changed the second stage calcination temperature of S6 from 460°C to 650°C, while the heating rate, holding time and other steps remained unchanged.
[0080] 1. Scanning electron microscopy observation and image analysis The scanning electron microscopy observations and image analyses described below are used to verify whether each sample forms particle structure features corresponding to the aforementioned technical effects, without considering image identifiability or parameter quantifiability itself as a technical effect. In this specification and claims, all references to the proportion of spherical particles, aspect ratio a / b, projected roundness C, equivalent circle diameter De, and particle size distribution obtained from particle size statistics are statistically analyzed according to the uniform conditions specified in this section. Each sample powder was adhered to conductive tape and sputtered with gold, then observed under a scanning electron microscope at an accelerating voltage of 15 kV. The original images used for particle outline and size statistics were uniformly magnified at 10000x, and the exported image resolution was no less than 2048×2048 pixels; five non-overlapping fields of view were pre-selected for each sample. Each field of view begins at the top left corner of the image and is scanned in a fixed order from left to right and top to bottom. Particles with complete outlines that do not intersect with the image boundaries are included in the count until 120 particles are found. If fewer than 120 particles meet the criteria in a single field of view, adjacent non-overlapping fields of view are randomly selected and the count is continued in the same order until 120 particles are found. A total of 600 particles are counted for each sample. During the count, no manual selection or rejection is allowed based on particle morphology or size. The same version of image analysis software, the same scale calibration method, and the same contour smoothing parameters are used for binarization and contour extraction. All absolute size statistics involving μm or nm are converted based on the scale or pixel-length calibration information corresponding to the original image exported from the scanning electron microscope. The overall scaling of the accompanying drawings during the layout process is only for morphology display and does not recalculate the absolute size of particles or surface protrusions based on the layout image size.
[0081] Ellipse fitting was performed on the two-dimensional projected profile of each particle, and the major axis a and minor axis b of the fitted ellipse were recorded. Roundness was calculated using C=4πA / P², where A is the projected area of the particle and P is the projected perimeter of the particle. The equivalent circle diameter was calculated using De=2√(A / π). Particles with a major-to-minor axis ratio of 1.00–1.50, a surface with fine protrusions forming granular undulations, and no obvious sharp edges were classified as quasi-spherical particles. The percentage of quasi-spherical particles out of the total number of particles was recorded as the quasi-spherical particle count percentage. The quasi-spherical particle count percentage in Table 1 uses the actual 600 particles counted for each sample as the denominator; the particle size range percentage in Table 2 uses the integer total number of quasi-spherical particles determined in Table 1 as the denominator. All percentages were calculated from the integer particle count and rounded to one decimal place. Except for the quasi-spherical particle count percentage, the following statistics on equivalent circle diameter distribution, two-level particle size, and surface texture all use quasi-spherical particles determined according to the above rules as the statistical object.
[0082] When performing quantitative statistics on surface protrusions, original images from scanning electron microscopes at 20,000 to 50,000x magnification were separately acquired, with image pixel-length calibration values not exceeding 5 nm / pixel. Five non-overlapping fields of view were randomly selected for each sample, and at least 50 surface protrusions with identifiable boundaries were measured in each field of view on the surface of the spherical particles.
[0083] The samples used for quantitative analysis of surface fine structures were coated with a conductive coating with a thickness of no more than 5 nm, and the same coating material and coating conditions were used for each sample to be compared.
[0084] The lateral dimension of the surface protrusion is the maximum projected width of a single protrusion along the tangential direction of the particle body surface.
[0085] Radial outward structure inspection was performed on each sample. The criteria for judgment were: the projection length extending outward from the main outline of the particle was greater than 300 nm and the ratio of the projection major axis to the projection minor axis was greater than 3. If no structure meeting the criteria was detected in 5 random high-power fields of view, it was recorded as not detected.
[0086] Two-stage particle size statistics were conducted using spherical particles as the statistical object, and a frequency histogram of equivalent circular diameters (De) was established with a group interval of 0.10 μm.
[0087] The second particle size range is 0.10–0.80 μm, and the first particle size range is 0.80–3.50 μm, where particles with De=0.80 μm are classified as particles of the second particle size.
[0088] When there is at least one local frequency maxima in the second particle size range and the first particle size range respectively, and there are one or more consecutive particle size groups with decreasing frequencies between the two local maxima, the sample is considered to have formed two particle size concentration regions.
[0089] For samples that form two particle size concentration zones, calculate the average De of the first particle size and the second particle size respectively, and calculate the ratio of their average De.
[0090] When the two-dimensional projected profile of the second-size particle is connected to the two-dimensional projected profile of the first-size particle, or when the two-dimensional projected centroid of the second-size particle is located in the interval region between the two-dimensional projected profiles of adjacent first-size particles, it is recorded as two-dimensional connection or interval distribution.
[0091] 2. Energy-dispersive X-ray spectroscopy detection At an accelerating voltage of 15 kV, three regions of each sample were randomly selected for energy-dispersive X-ray spectroscopy scanning, and the detection of characteristic peaks for iron, manganese, and oxygen was recorded. This detection was used to confirm the simultaneous presence of iron, manganese, and oxygen in the sample particles, and was not used to determine the valence state or crystal phase of elements.
[0092] 3. Testing of powder accumulation and constant pressure compaction performance Each sample was dried under vacuum at 80℃ for 2 h and then cooled to room temperature in a desiccator. For the tapped density test, 20.00 g of sample was weighed and added to a 25 mL graduated cylinder. A mechanical tapping device was used to tap the sample 1250 times at a rate of 250±15 times / min and an amplitude of 3.0±0.2 mm. If the volume change was still greater than 1% after 500 taps, the process was repeated in sets of 500 taps until the volume change between two consecutive records was no greater than 1%. The final tapped volume Vt was recorded, and the tapped density was calculated using ρt=m / Vt. Each sample was tested in triplicate.
[0093] During the constant pressure compaction density test, a 1.000 g sample was weighed and placed into a cylindrical mold with an inner diameter of 13.00 mm. The sample was held under a pressure of 100 MPa for 60 s, and after depressurization, it was allowed to stand for 10 min. The diameter d and thickness h of the compacted sample were measured, and the result was calculated according to ρc=m / [π(d / 2). 2 h] Calculate the compaction density. Each sample was tested in triplicate, and the results are expressed as mean ± standard deviation. This test is used to compare the packing density and compaction state of samples under the same vibration and compaction conditions, and is not directly equivalent to the actual particle contact area or electrochemical interface area.
[0094] Table 1 Statistical results of particle outer contour Example 1 600 86.3 1.04~1.29 0.76~0.94 Example 2 600 95.2 1.02~1.21 0.82~0.97 Example 3 600 52.7 1.08~1.47 0.72~0.91 Example 4 600 72.0 1.02~1.28 0.78~0.97 Comparative Example 1 600 46.8 1.10~1.78 0.62~0.88 Comparative Example 2 600 84.0 1.05~1.32 0.75~0.93 Comparative Example 3 600 85.8 1.03~1.30 0.75~0.94 Table 2 Statistical results of equivalent circle diameter distribution Example 1 0.07~3.82 93.6 84.2 Example 2 0.82~3.74 96.8 96.8 Example 3 0.08~3.78 82.9 63.9 Example 4 - - - Comparative Example 1 0.06~3.90 92.2 81.1 Comparative Example 2 0.08~3.66 94.0 90.1 Comparative Example 3 0.07~3.70 93.0 84.1 Table 3 Statistical results of the two-stage particle size and two-dimensional positional relationship Example 1 0.86~3.18 0.16~0.76 4.56:1 58.7 Example 2 not applicable not applicable not applicable not applicable Example 3 0.84~3.42 0.12~0.78 2.23:1 38.3 Example 4 not applicable not applicable not applicable not applicable Comparative Example 1 0.88~3.12 0.16~0.74 4.40:1 55.0 Comparative Example 2 not applicable not applicable not applicable not applicable Comparative Example 3 0.86~3.16 0.15~0.76 4.48:1 56.0 Table 4 Statistical results of surface texture Example 1 34~168 0.059 Not detected Example 2 30~120 0.052 Not detected Example 3 26~186 0.184 Not detected Example 4 - - Not detected Comparative Example 1 35~170 0.060 Not detected Comparative Example 2 33~165 0.058 Not detected Comparative Example 3 6~18 0.009 Not detected Table 5. Elemental detection results of energy-dispersive X-ray spectroscopy Example 1 Fe, Mn, O Iron, manganese and oxygen coexist Example 2 Fe, Mn, O Iron, manganese and oxygen coexist Example 3 Fe, Mn, O Iron, manganese and oxygen coexist Example 4 Fe, Mn, O Iron, manganese and oxygen coexist Comparative Example 1 Fe, Mn, O Iron, manganese and oxygen coexist Comparative Example 2 Fe, Mn, O Iron, manganese and oxygen coexist Comparative Example 3 Fe, Mn, O Iron, manganese and oxygen coexist Table 6 Results of Powder Vibration Compaction and Constant Pressure Compaction Example 1 1.84±0.03 3.14±0.04 Example 2 1.76±0.02 3.00±0.03 Example 3 1.69±0.03 2.88±0.05 Example 4 1.71±0.03 2.91±0.04 Comparative Example 1 1.42±0.04 2.49±0.06 Comparative Example 2 1.60±0.03 2.69±0.05 Comparative Example 3 1.80±0.03 3.07±0.04 As shown in Tables 1, 2 and 4, the proportion of spherical particles in Examples 1 to 4 is not less than 50%, and the proportion of spherical particles in Examples 1, 2 and 4 is not less than 70%; the a / b ratio and projected roundness C of the corresponding spherical particles are all within the defined range.
[0095] In Examples 1 to 3, the proportions of quasi-spherical particles with a diameter of 0.10–3.50 μm were 93.6%, 96.8%, and 82.9%, respectively, and the proportions of quasi-spherical particles with a diameter of 0.30–3.20 μm were 84.2%, 96.8%, and 63.9%, respectively, indicating that the main quasi-spherical particles in the corresponding samples were concentrated within a controlled micron-sized particle size range.
[0096] The ratios of the average lateral dimension of the surface protrusions to the average De of the spherical particles in Examples 1, 2, and 3 are 0.059, 0.052, and 0.184, respectively, all within the range of 0.05 to 0.20.
[0097] Example 4 is mainly used to illustrate that under the boundary combination of process parameters, it can still maintain a spherical body, granular surface undulation and no obvious long radial outward structure, and is no longer used as a quantitative boundary sample for particle size ratio conditions or size ratio lower limit. Figure 1 and Figure 2 In the representative scanning electron microscope images of Example 1, most particles have rounded outlines, and smaller particles are observed distributed among larger particles, corresponding to the overall morphology and statistical results of the spatial arrangement of the two-level particles shown in Tables 1 and 3. This morphological combination provides a structural basis for the uniform arrangement of particles and subsequent particle contact and interfacial interactions.
[0098] As shown in Table 3, in the equivalent circle diameter frequency distributions of Examples 1 and 3, particle size concentration regions are formed within the first and second particle size ranges, respectively, with average De ratios of the two types of particles being 4.56:1 and 2.23:1, respectively. In the two-dimensional projection images, the proportions of particles with the second particle size that are in contact with the outlines of particles with the first particle size or located in the interval region between adjacent particles with the first particle size in Examples 1 and 3 are 58.7% and 38.3%, respectively, both not less than 35%.
[0099] The above results indicate that the obtained powder not only has particles of different sizes coexisting, but also that the smaller particles form a positional fit relationship with the larger particles in a two-dimensional projection with a certain statistical proportion, providing a structural basis for supplementing and filling the gaps between particles.
[0100] Example 1 differs from Comparative Example 1 only in the timing of ammonium bicarbonate addition in the first stage. In Example 1, 45% of the total ammonium bicarbonate solution was continuously added within 60 minutes, and the proportion of near-spherical particles was 86.3%. In Comparative Example 1, after shortening the addition time to 10 minutes, the proportion of near-spherical particles decreased to 46.8%, and the upper limit of a / b for all particles included in the statistics increased to 1.78. Figure 9 and Figure 10 In the representative scanning electron microscope image of Comparative Example 1 shown, an increased proportion of polyhedral, truncated, and irregularly shaped particles can be observed. This result indicates that adding the precipitant too quickly in the first stage increases the local instantaneous supersaturation, which is detrimental to the uniform control of particle nucleation and early growth processes.
[0101] In Comparative Example 2, after the second-stage pH gradual increase process was eliminated, although particles of different sizes still existed, two particle size concentration zones that met the criteria of this application were not formed, and its tapped density and constant-pressure compaction density decreased to 1.60 g / cm³. 3 and 2.69 g / cm 3 This indicates that the combination of gradually increasing the pH and decreasing the stirring speed in the second stage is beneficial for changing the subsequent sedimentation and growth state, thereby forming a more clearly defined particle size hierarchy.
[0102] Figure 12 and Figure 13 After the second heat treatment at 650℃, the particle surface of Comparative Example 3 showed a significant smoothing, with the lateral dimensions of the protrusions decreasing to 6–18 nm, and the ratio of the average protrusion size to the average De decreasing to 0.009. This indicates that excessively high second-stage heat treatment temperatures exacerbate the sintering and passivation of fine surface structures, thereby weakening the desired granular texture. However, the tap density and compacted density of Comparative Example 3 still reached 1.80 g / cm³. 3 and 3.07 g / cm 3 This is similar to Example 1, indicating that the fine surface undulations of 20–200 nm are not the main determining factor for improving stacking and compaction performance.
[0103] As shown in Table 6, under the same test conditions, the tapped density and the compacted density at 100 MPa in Example 1 were 1.84 g / cm³. 3 and 3.14 g / cm 3Compared to Comparative Example 1, the yields increased by approximately 29.6% and 26.1%, respectively; compared to Comparative Example 2, which did not form a two-stage particle size structure, the yields increased by approximately 15.0% and 16.7%, respectively. Combined with Tables 1 and 3, it can be seen that the higher proportion of spherical bodies and the two-dimensional positional relationship between the second-size particles and the first-size particles are beneficial for particle rearrangement and reducing interparticle voids during compaction and compression, thereby improving the density of powder packing and compaction. The compaction density and vibration density of Comparative Example 3 are quite close to those of Example 1, indicating that this test mainly reflects the influence of the overall particle profile and particle size distribution on the packing / compaction state, while the effect of surface undulations in the 20–200 nm range is still mainly reflected in the surface structure basis, and it is not appropriate to directly infer the actual increase in interface area based solely on this test.
[0104] The above results demonstrate that the aforementioned phased process can synergistically obtain a more regular spherical body, a reasonable particle size distribution, and appropriate surface undulations. It also reduces local bridging and contact dispersion caused by irregular particles, which is beneficial to improving the packing density and compaction of the powder and provides a structural basis for subsequent interfacial interactions.
[0105] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A quasi-spherical iron-manganese oxide composite material, characterized in that, The composite material is a powder with a chemical composition including iron, manganese and oxygen elements, and the powder contains spherical particles; the number of spherical particles accounts for no less than 50% of the total number of particles whose outer contours can be identified in a scanning electron microscope image; the ratio of the major axis a to the minor axis b of the two-dimensional projected outer contour of the spherical particles obtained by ellipse fitting is 1.00 to 1.50, and the surface of the spherical particles has a granular undulating texture composed of fine protrusions.
2. The near-spherical iron-manganese oxide composite material according to claim 1, characterized in that, The number of spherical particles accounts for no less than 70%, the ratio of the major axis a to the minor axis b of the spherical particles (a / b) is 1.00 to 1.30, and the projected roundness C of the spherical particles is 0.70 to 1.00, where C = 4πA / P. 2 Where A is the two-dimensional projected area of the spherical particle, and P is the two-dimensional projected outer contour perimeter of the spherical particle.
3. The near-spherical iron-manganese oxide composite material according to claim 1 or 2, characterized in that, Based on the number of the quasi-spherical particles, at least 80% of the quasi-spherical particles have an equivalent circular diameter of 0.10 to 3.50 μm, and at least 60% of the quasi-spherical particles have an equivalent circular diameter of 0.30 to 3.20 μm, wherein the equivalent circular diameter De = 2√(A / π).
4. The near-spherical iron-manganese oxide composite material according to any one of claims 1 to 3, characterized in that, The projected lateral dimension of the surface protrusions forming the granular undulating texture is 20-200 nm, and the ratio of the average projected lateral dimension of the surface protrusions to the average equivalent circle diameter of the spheroidal particles is 0.05-0.
20. In the scanning electron microscope image, five non-overlapping fields of view were randomly selected, and no needle-like, rod-like, or sheet-like structures extending outward from the main outline of the spheroidal particles, with a projected length greater than 300 nm and a ratio of the projected major axis to the projected minor axis greater than 3 were detected.
5. The near-spherical iron-manganese oxide composite material according to any one of claims 1 to 4, characterized in that, The frequency distribution of the equivalent circular diameter of the quasi-spherical particles has two particle size concentration regions located in the ranges of 0.10–0.80 μm and 0.80–3.50 μm, respectively. Particles located in the range of 0.80–3.50 μm are designated as first-size particles, and particles located in the range of 0.10–0.80 μm are designated as second-size particles. Particles with an equivalent circular diameter equal to 0.80 μm are classified as second-size particles. The ratio of the average equivalent circular diameter of the first-size particles to that of the second-size particles is 2.0–10.0:
1.
6. The near-spherical iron-manganese oxide composite material according to claim 5, characterized in that, Based on the number of particles of the second size in the two-dimensional projection image of a scanning electron microscope, at least 35% of the two-dimensional projection profiles of the particles of the second size are connected to the two-dimensional projection profiles of the particles of the first size, or their two-dimensional projection centroids are located in the interval region between the two-dimensional projection profiles of adjacent particles of the first size.
7. A method for preparing a near-spherical iron-manganese oxide composite material according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Add divalent manganese salt and trivalent ferric salt to water, and add complexing agent and dispersing component to obtain metal salt solution; The divalent manganese salt is manganese sulfate monohydrate, and the trivalent iron salt is ferric sulfate nonhydrate or ferric nitrate nonhydrate; the molar ratio of Mn to Fe is 4.8:1 to 13.8:1 based on the amount of Mn and Fe. The total mass ratio of the divalent manganese salt and the trivalent iron salt to the mass of water is 12:(50-100); Based on the total mass of the divalent manganese salt and trivalent iron salt, the amount of the complexing agent is 9.5% to 13.0%, and the amount of the dispersing component is 1.0% to 1.5%. The complexing agent is selected from at least one of sodium citrate, sodium tartrate, sodium gluconate, and disodium ethylenediaminetetraacetate, and the dispersing component is selected from at least one of polyvinylpyrrolidone, polyethylene glycol, and sodium polycarboxylate; The ratio of the total amount of ammonium bicarbonate used to the total amount of manganese and iron is 1.15:1; S2. Under the conditions of stirring at 48-55℃ and 600-700 r / min, continuously add 35%-50% of the total amount of ammonium bicarbonate solution within 40-120 min, and control the pH of the system at 6.6-6.9 by adding ammonia water to carry out the first stage of co-precipitation. S3. Reduce the stirring speed to 180-220 r / min, continuously add the remaining ammonium bicarbonate solution over 90-180 min, and gradually increase the pH of the system from the first stage to 7.8-8.3 by adding ammonia water during the feeding process, and carry out the second stage co-precipitation to obtain the precursor slurry. S4. Concentrate the precursor slurry to a solid content of 24% to 35%, let it stand at 58 to 75°C for 50 to 120 min, and then stir it at 100 to 150 r / min for 80 to 180 min to mature it. S5. The matured precursor slurry is subjected to solid-liquid separation, washing and drying to obtain a dried precursor. S6. The dried precursor is subjected to segmented heat treatment. First, it is kept at 180-230℃ for 50-90 min, then heated to 360-480℃ and kept at that temperature for 90-240 min. After cooling, the spherical iron-manganese oxide composite material is obtained.
8. The preparation method according to claim 7, characterized in that, In step S2, 40% to 50% of the total amount of ammonium bicarbonate solution is added within 50 to 80 minutes. The temperature of the first stage co-precipitation is 48 to 52°C, the stirring speed is 600 to 650 r / min, and the pH of the system is 6.7 to 6.
9.
9. The preparation method according to claim 7 or 8, characterized in that, In step S3, the remaining ammonium bicarbonate solution is added within 90 to 120 minutes, and the pH of the system is gradually increased from 6.7 to 6.9 to 8.0 to 8.3 during the addition process.
10. The preparation method according to any one of claims 7 to 9, characterized in that, In step S6, the temperature is first kept at 210-230℃ for 50-60 minutes, and then raised to 440-480℃ and kept at that temperature for 90-120 minutes.
Citation Information
Patent Citations
Ferro-manganese composite oxide as well as preparation method and application thereof in removing arsenic in water
CN103212364A
Fe / Mn composite oxide, preparation method and application thereof
CN104815609A